PACAP38 synergizes with irradiation to suppress the proliferation of multiple cancer cells via regulating SOX6/Wnt/β-catenin signaling - Wu, Ran; Cao, Chun-Xiang; Cao, Lu; Su, Jun; Liao, Ke-Man; Li, Huan; Zhu, Qian; Li, Shu-Yan; Li, Min; Chen, Jia-Yi (Frontiers in Pharmacology, 2024)
Background: Pituitary adenylate cyclase-activating polypeptide (PACAP) 38 is an endogenous neuropeptide with diverse functions, notably its critical role in inhibiting tumor proliferation. Radiotherapy is an important step in the standard treatment modality of many tumors. Combining radiotherapy with therapeutic agents represents a new and promising trend aimed at enhancing radiation sensitivity and improving tumor treatment efficacy. However, the efficacy of PACAP38 combined with radiotherapy on tumors has not yet been studied. Objective: This study aimed to investigate the impact of PACAP38, both independently and in combination with irradiation, on glioma and breast cancer cells, , while elucidating the underlying mechanisms involved. Method: We investigated the impact of PACAP38 independently and combined it with irradiation on glioma and breast cancer cells in vitro through cell counting kit-8, clonogenic formation, Edu assays, and in vivo through a xenograft tumor model. We further explored the molecular mechanisms underlying the inhibitory effects of PACAP38 on tumors using RNA sequencing, western blotting assay, immunohistochemistry, and immunofluorescence analysis. Further investigation of gene function and the downstream mechanism was carried out through small interfering RNA and overexpression lentivirus targeting the SRY-related high-mobility group box 6 (SOX6) gene and western blotting assay. Results: Our findings revealed that PACAP38 could effectively synergize with radiation to suppress the proliferation of glioma and breast cancer cells in vivo and in vitro. Molecular studies revealed that the inhibitory effect of PACAP38 on tumor cell proliferation was mediated by upregulating SOX6 protein expression through histone acetylation, thereby inhibiting the Wnt-β-catenin signaling pathway. Conclusion: PACAP38 synergizes with irradiation to suppress the proliferation of multiple cancer cells via regulating SOX6/Wnt/β-catenin signaling. This combination may represent a promising therapeutic strategy for cancer treatment, potentially improving outcomes for patients undergoing radiotherapy.